2010
DOI: 10.1007/bf03216930
|View full text |Cite
|
Sign up to set email alerts
|

Issues and challenges in higher education leadership: Engaging for change

Abstract: It is proposed from this study that engaging productively with others to achieve change has never been more critical in educational environments, such as universities. Via semi-structured interviews with a cohort of senior leaders from one Australian university, this paper explores their perceptions of the key issues and challenges facing them in their work. The study found that the most significant challenges centred around the need for strategic leadership, flexibility, creativity and change-capability; resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 22 publications
0
47
0
1
Order By: Relevance
“…More specifically and given the importance of the challenges in the literature, it was found that most of the identified challenges had been addressed in previous research works. For example, identified challenges related to funding (Keener et al, 2002;Shin & Harman, 2009;Teixeira & Koryakina, 2013), staff management and human resources (Drew, 2010;Fullan & Scott, 2009;Keener et al, 2002), as well as red tape and bureaucracy (Black, 2015;Fullan & Scott, 2009;Teferra & Altbach, 2004) may be specified. In addition, other challenges, which were in alignment with the findings in other research works, included workloads and the nature of academic work (Black, 2015;Ramsden, 1998), collaborations (Black, 2015;Drew, 2010), commitment and loyalty (Black, 2015), lack of time and time management skills (Drew, 2010), and providing supporting services (Fullan & Scott, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically and given the importance of the challenges in the literature, it was found that most of the identified challenges had been addressed in previous research works. For example, identified challenges related to funding (Keener et al, 2002;Shin & Harman, 2009;Teixeira & Koryakina, 2013), staff management and human resources (Drew, 2010;Fullan & Scott, 2009;Keener et al, 2002), as well as red tape and bureaucracy (Black, 2015;Fullan & Scott, 2009;Teferra & Altbach, 2004) may be specified. In addition, other challenges, which were in alignment with the findings in other research works, included workloads and the nature of academic work (Black, 2015;Ramsden, 1998), collaborations (Black, 2015;Drew, 2010), commitment and loyalty (Black, 2015), lack of time and time management skills (Drew, 2010), and providing supporting services (Fullan & Scott, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Other main identified challenges include academic leadership challenges (Black, 2015;Drew, 2010;Fullan & Scott, 2009), sustainability challenges in HE (Mader, 2012;Mader, Scott, & Razak, 2013;, university mergers and transnational virtual delivery of HE (Van Damme, 2001;Yung-Chi Hou, Morse, & Wang, 2015), challenges pertinent to embedding a quality culture in universities (Lomas, 2004), gender issues in HE (Baker, 2016;Cotterill & Letherby, 2005), and the challenges of merging divergent campus cultures to form coherent educational communities (Harman, 2002).…”
Section: Research-article20182018mentioning
confidence: 99%
“…Along with a series of leader interventions, leaders also need to develop their leadership capabilities (Drew 2010).…”
Section: Leading Systemic Changementioning
confidence: 99%
“…Organisational change has become an important part of educational change involving sustained change in the long run (Boyce 2003;Drew 2010). Changing curriculum and changing university organisations is a continuous process of negotiation, facilitated by leaders within the university.…”
Section: Faculty Development As Leader Interventionmentioning
confidence: 99%
“…Most leaders andfaculty members relate leadership of top leaders to exercise their power (autocratic).On the other hand, the leadership approach of middle-level leaders, such as program Leaders and trade heads differs from that of the top leaders. The middlelevelleaders state that they follow a democratic or follower-oriented leadership approach, suchas being friendly, considerate and building trust (Drew, 2010) through the use of moreconsultative and consensus seeking styles. Their leadership ranges from the 'Manager presentstentative decisions subject to change' to the 'Manager defines limits, asks to make decision'.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%